Towards Effective and Accountable Leadership of the Union- Options and Guidelines for reform (part two) - Wouter Coussens; Ben Crum (Romanian Journal of European Affairs)
The success of the Convention on the future of the EU will to a great extent depend upon on its answers to the institutional questions. Among these questions, the issue of EU leadership plays a crucial role. In this paper, three challenges for the re-organisation of leadership in the Union are identified: – Union leadership has to be more effective; – Leadership in the Union should contribute to the democratic character of the Union; – Leadership reform should not fundamentally distort the Union’s institutional balance. In view of these three challenges, the authors consider the two main strands of debate that touch upon the issue of leadership in the EU: first, the debate on the election of the Commission President and, secondly, the different proposals for reforming the Council Presidency.